2001
DOI: 10.1034/j.1600-0536.2001.440205.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of occupational hand dermatitis in bakers, confectioners and employees in the catering trades

Abstract: Occupational skin diseases (OSD) are among the most frequent occupational diseases (OD). Compared to other occupations, bakers, confectioners and employees in the catering trades are at a high risk of developing OSD. In January 1999, the interdisciplinary Skin Disease Prevention Program in the Baking, Hotel and Catering Industries (SDPP) conducted by the Department of Dermatology and Allergology at the Friedrich Schiller University, Jena, in cooperation with the Research Center for Applied System Safety and In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 15 publications
1
32
0
6
Order By: Relevance
“…In the past, at the level of secondary prevention of OSD it could be proven that combined dermatological and health educational prevention measures are successful; in several recent studies the success was shown to be dependant on the degree of implementation of the recommended skin protection by the study participants and of continuous or repeated interdisciplinary intervention (Bauer et al 2001;Held and Agner 2006;Nienhaus et al 2004;Schurer et al 2005;Weisshaar et al 2006;Wulfhorst et al 2006). The higher rates of the job-continuation at the level of the secondary prevention [e.g.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the past, at the level of secondary prevention of OSD it could be proven that combined dermatological and health educational prevention measures are successful; in several recent studies the success was shown to be dependant on the degree of implementation of the recommended skin protection by the study participants and of continuous or repeated interdisciplinary intervention (Bauer et al 2001;Held and Agner 2006;Nienhaus et al 2004;Schurer et al 2005;Weisshaar et al 2006;Wulfhorst et al 2006). The higher rates of the job-continuation at the level of the secondary prevention [e.g.…”
Section: Discussionmentioning
confidence: 95%
“…For secondary prevention, in Germany, the so-called dermatologist's procedure was recently modernised in order to provide more rapid dermatological consultations for aVected employees (Dickel et al 2004;John et al 2004). Besides, the usefullness of combined medical and educational intervention programmes could be demonstrated (Bauer et al 2001;Diepgen et al 2005;Held and Agner 2006;Nienhaus et al 2004;Schurer et al 2005;Weisshaar et al 2006;Wulfhorst et al 2006). For those cases of OSD, in which these out-patient prevention measures are not successful, we have developed speciWc interdisciplinary in-patient prevention measures, the so called tertiary individual prevention (TIP).…”
Section: Introductionmentioning
confidence: 95%
“…More than half of all OCD is experienced in the first 2 years of commencing work [20] due to poor knowledge of agents responsible and poor skin hygiene. This justifies establishing educational programmes in different professional sectors [40], in particular for cleaning and maintenance employees [41], apprentice bakers [42], restaurant workers [43], hairdressers [44,45], student nurses [46], and workers in the chemical [47] and metallurgical industries [48]. Ideally, educational measures should be put in place before a new employee starts work, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…W takich przypadkach ochronę stanowią środki ochrony skóry. Środki ochrony skóry są zalecane do stosowania na stanowiskach pracy i w profilaktyce dermatoz skóry rąk (6)(7)(8). Preparaty te, rozprowadzone po powierzchni skóry, pokrywają ją cienką warstwą i tworzą film ochronny -nie wnikają w głąb (jak to ma miejsce w przypadku kremów pielęgnacyj-nych).…”
Section: Wstępunclassified